Cardiac Insulin Signaling Regulates Glycolysis Through Phosphofructokinase 2 Content and Activity. Issue 12 (4th December 2017) - Bockus, Lee B.; Matsuzaki, Satoshi; Vadvalkar, Shraddha S.; Young, Zachary T.; Giorgione, Jennifer R.; Newhardt, Maria F.; Kinter, Michael; Humphries, Kenneth M.
Abstract : Background: The healthy heart has a dynamic capacity to respond and adapt to changes in nutrient availability. Diabetes mellitus disrupts this metabolic flexibility and promotes cardiomyopathy through mechanisms that are not completely understood. Phosphofructokinase 2 (PFK‐2) is a primary regulator of cardiac glycolysis and substrate selection, yet its regulation under normal and pathological conditions is unknown. This study was undertaken to determine how changes in insulin signaling affect PFK‐2 content, activity, and cardiac metabolism. Methods and Results: Streptozotocin‐induced diabetes mellitus, high‐fat diet feeding, and fasted mice were used to identify how decreased insulin signaling affects PFK‐2 and cardiac metabolism. Primary adult cardiomyocytes were used to define the mechanisms that regulate PFK‐2 degradation. Both type 1 diabetes mellitus and a high‐fat diet induced a significant decrease in cardiac PFK‐2 protein content without affecting its transcript levels. Overnight fasting also induced a decrease in PFK‐2, suggesting it is rapidly degraded in the absence of insulin signaling. An unbiased metabolomic study demonstrated that decreased PFK‐2 in fasted animals is accompanied by an increase in glycolytic intermediates upstream of phosphofructokianse‐1, whereas those downstream are diminished. Mechanistic studies using cardiomyocytes showed that, in the absence of insulin signaling, PFK‐2 is rapidly degraded via both proteasomal‐ and chaperone‐mediated autophagy. Conclusions: The loss of PFK‐2 content as a result of reduced insulin signaling impairs the capacity to dynamically regulate glycolysis and elevates the levels of early glycolytic intermediates. Although this may be beneficial in the fasted state to conserve systemic glucose, it represents a pathological impairment in diabetes mellitus.